HUBUNGAN KARAKTERISTIK DENGAN KEPUASAN PASIEN PENGGUNA BPJS KESEHATAN DI PUSKESMAS CIMAREME BERDASARKAN PERSEPSI PASIEN - Nur Saffanah, Hasya; Setiawati, Setiawati; Oyoh, Oyoh; Rohayani, Lilis; Inayah, Iin (Yayasan Healing and Healthcare Education, 2023)
Patient satisfaction is a multidimensional concept because many factors play a role in determining patient satisfaction. The aim of taking this title is to determine whether or not there is a relationship between characteristics and satisfaction. According to the 2021 Cimareme Health Center profile, the number of patient visits was 23,483. analytical survey research with a cross sectional research design. The sample in this study was 89 BPJS patients with a population of 797 people. The sampling method in this research used the Random Sampling method with the Accidental sampling technique. The results of the univariate analysis of the characteristics of the respondents, elderly 47 people (52.8%), female sex 64 people (71.9%), secondary education 54 people (60.7%) and non-PNS jobs 87 people (97.8%). Patient satisfaction is satisfied 44 people (49.4%), less satisfied 43 people (48.3%). The results of bivariate analysis between age and patient satisfaction p value = 0.940 > α = 0.05 then there is no relationship, gender and patient satisfaction p value = 0.148 > α = 0.05 then there is no relationship, education with patient satisfaction p value = 0.004 > α = 0.05 then there is a relationship, work with patient satisfaction p value = 0.335 > α = 0.05 then there is no relationship, suggestions for puskesmas to be able to pay attention to things that patients feel unsatisfied with.